2011
DOI: 10.1007/s11604-011-0567-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal impairment by non-contrast-enhanced conventional magnetic resonance imaging: comparison with 99mTc-DTPA renography

Abstract: Non-contrast-enhanced MRI was capable of distinguishing three levels of renal function, including serious renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…14 Our present results in patients with CKD without liver cirrhosis are consistent with this previous result.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…14 Our present results in patients with CKD without liver cirrhosis are consistent with this previous result.…”
Section: Discussionsupporting
confidence: 93%
“…Second, we excluded patients with apparent asym- metry of the kidneys because SKGFR was not estimated using a nuclear medicine study or perfusion MR imaging. 1,14 We cannot therefore extrapolate our present results to patients with CKD who have unilateral renal atrophy. Third, the observers were not completely blinded to whether the subjects belonged to the group with cirrhosis or the comparative group because liver cirrhosis was often obvious on the T 1 -weighted images.…”
Section: Discussionmentioning
confidence: 78%
“…Third, CMD as observed on the T1-weighted images was defined as good, moderate, or poor, based on previous studies as follows: good, CMD was visualized clearly throughout the kidney; moderate, CMD was partially lost in the kidney; poor, CMD was diminished. [12,13] The CMD was compared with renal function in these older patients with GCK. A kappa analysis was used to evaluate the radiologists’ assessment of CMD.…”
Section: Methodsmentioning
confidence: 99%
“…[5,10,11] In these studies, T1-weighted MRI detects renal impairment as the loss of corticomedullary differentiation (CMD). [10,12] Therefore, MRI may be an ideal imaging tool for identifying GCK. We identified 13 older patients with GCK during routine abdominal MRI.…”
Section: Introductionmentioning
confidence: 99%
“…2 Meanwhile, renal cortical volumes and cortical thicknesses have been found to correlate with renal function. [6][7][8][9][10][11][12][13] It has been reported that non-contrast-enhanced steady-state free precession (SSFP) MRI with a spatially selective inversion recovery (IR) pulse can emphasize the difference in T 1 values between the renal cortex and the medulla by suppressing the background signal and the target tissue signal. Therefore, compared with conventional MRI sequences, this technique can improve the visualization of renal corticomedullary differentiation and facilitate the measurement of renal cortical thickness even in patients with renal dysfunction compared with conventional MRI sequences.…”
Section: Introductionmentioning
confidence: 99%